Pronunciation Ability Improvement by Resso Application at The Parepare Senior High School Students - Aisyah Ramadani; Kalsum Kalsum; Ahmed Sardi; Agussalim Agussalim (Universitas Muhammadiyah Barru, 2024)
This research was aimed to find out the improvement of students’ pronunciation ability. This research applied quantitative approach and used quasi experimental design. The population was taken from the second-grade students of SMA Negeri 2 Parepare. The samples in this research were 72 students of experimental and control class. The researcher analyzed the data used t-test formula. The result of the research showed that the English songs technique can improve students’ pronunciation. The mean score of experimental class is 89.72 and the mean score of control class is 54.027. It means that the mean score of experimental class is higher than control class. For the level significant (ɑ) 5% and df = 34 and the value of table is 1,697 while the value of t-test 22,54. It means that the t-test value was greater that t-table value 1,697 table (22,54 ≥ 1.697). On the other word, (Ha) was accepted and (H0) was rejected. It can be concluded that there is a significant difference between students’ pronunciation ability that were taught through Resso’s English song and students who were not taught trough Resso’s English song at SMA Negeri 2 Parepare. It can be underlined that the usage Resso Application gives a great contribution in teaching and learning process on the students’ pronunciation improvement because Resso Application has a good effect. It becomes important for the teachers to increase and develop students’ pronunciation ability.